Osteochondroma pada Pasien Perempuan Usia 15 tahun di Rumah Sakit Umum Daerah Cut Meutia Aceh Utara - Islah Salsabila; Muhammad Bayu Rizaldy (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2026)
Osteochondroma, also known as osteocartilaginous exostosis or cartilage-capped exostosis, is a bony protrusion on the surface of a bone that may appear broad-based (sessile) or stalk-like (pedunculated), and is covered by a cartilage cap. Osteochondroma can arise from the medullary cavity or cortical bone. A patient presented to the Orthopedic Surgery Clinic at Cut Meutia General Hospital with a complaint of a lump on the left arm, specifically on the upper arm region. The patient reported that the lump initially appeared small but had gradually increased in size over the past six months. On physical examination, a firm, immobile mass measuring approximately 4.5 × 4.5 cm was found. The lump was painful, and the pain was exacerbated by palpation and arm movement, resulting in limited motion of the left upper extremity. The patient denied any history of trauma or radiation exposure. Laboratory findings were within normal limits. Radiographic examination of the left humerus revealed a mass located on the proximal one-third of the humerus. Anatomical pathology examination showed findings suggestive of osteochondroma. Based on the anamnesis, physical examination, and supporting investigations, the patient was diagnosed with a bone tumor consistent with osteochondroma. Radiographic imaging of the left humerus demonstrated a pedunculated lesion with a stalk-like appearance resembling a “cauliflower,” projecting away from the joint. The articular space appeared normal without narrowing, and there was calcification surrounded by cartilaginous tissue. A wide excision procedure was performed to remove the tumor tissue completely. The excised specimen was then sent for histopathological examination, which confirmed the diagnosis of osteochondroma. Postoperatively, the patient was educated about the condition and advised to maintain a healthy lifestyle and consume nutritious food. Because the patient received appropriate and timely treatment, the prognosis was considered good.